1993
DOI: 10.1002/chir.530050608
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the enantiomers of verapamil in the dog

Abstract: The intravenous (0.5 mg/kg) and oral (5 mg/kg) dose kinetics of verapamil were studied in 6 dogs during steady-state oral verapamil dosing (5 mg/kg every 8 h for 3 days). Racemic verapamil and norverapamil, a metabolite of verapamil, were quantitated in plasma by HPLC-fluorescence detection. The verapamil peaks eluting off the column were collected and rechromatographed on an Ultron-OVM column, which resolved the two verapamil enantiomers. After intravenous administration, the systemic clearance and apparent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The pharmacokinetics of enantiomers of verapamil have also been studied in dogs and rabbits. 4,10 Bai et al 10 reported stereoselective disposition of verapamil in dogs and found that the Cl s , Cl o and V db values of S-verapamil were greater than those of R-verapamil and that the oral bioavailability of R-verapamil was 14 times greater than that of S-verapamil. These dierences between the bioavailabilities of the enantiomers in dogs were much greater than that found (fourfold) in man.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetics of enantiomers of verapamil have also been studied in dogs and rabbits. 4,10 Bai et al 10 reported stereoselective disposition of verapamil in dogs and found that the Cl s , Cl o and V db values of S-verapamil were greater than those of R-verapamil and that the oral bioavailability of R-verapamil was 14 times greater than that of S-verapamil. These dierences between the bioavailabilities of the enantiomers in dogs were much greater than that found (fourfold) in man.…”
Section: Discussionmentioning
confidence: 99%
“…4,6±10 Although the kinetics of the individual enantiomers of verapamil in human have been extensively studied, a review of the literature reveals that there is a scarcity of stereospeci®c studies of verapamil in animals. 4,10 In view of the increasing interest in interspecies scaling up of absorption 11,12 and disposition kinetics 13±15 and of the ®ndings that the rat may serve as a good model for the human in p.o. absorption, 10 it was decided to study, in detail, the kinetics of verapamil enantiomers in male Sprague±Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of stereoselective plasma binding of drugs ranges up to a factor of about 1.5, reflecting a diastereomeric association with both albumin, the major binding protein for most acids (warfarin, ketoprofen [25], zopiclone [26]) and with AGP, which binds predominantly basic compounds (verapamil [27], propranolol [28]). Propranolol illustrates a case where the stereoselectivity of binding occurs in opposite directions for the different proteins.…”
Section: Understanding To Drug Interactions With Biological Systemsmentioning
confidence: 99%
“…Moreover, its use for the treatment of hypertension during ontogeny has been postulated [5,6]. The pharmacokinetics of verapamil has been described in dogs, rats, rabbits and humans [7][8][9][10]. This drug is extensively metabolised by N-demethylation, N-dealkylation and Odemethylation [4,11].…”
Section: Introductionmentioning
confidence: 99%